Analysis of Method C5.0 in Triggering Factors The Number of Covid-19 Increases or Decreases After Getting the Vaccine - Tanzil, Alferedo; Barasa, Randy Aldany; Laia, Yonata; Banjarnahor, Jepri (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Because we now know that many things make everyone sick, such as fever, flu, cough, and other diseases that are said to be easily transmitted, we need a system that can overcome the above problems. This study uses the K-NN method to examine what factors influence the increase in the number of people infected with Covid-19. The factors tested in this study were frequent violations of health practices, overcrowding, and weak immune systems. The K-NN method can overcome the problem of knowing the factors causing the increase in Covid-19 patients after vaccination.